New Dimension of Space in the Context of Needs People with Disabilities (Economic and Political Thought, 2023)
Conscious shaping of space is nowadays an indisputable challenge, but also a requirement addressed to the state in connection with the dynamically changing needs of society. The state’s increasing concern for its citizens has resulted in changes, also in terms of public space and the needs of people with disabilities. New instruments and institutions are being created and actions are being taken to adapt space so that people with special needs have at least minimal access to urban infrastructure. The aim of this study is to characterize the needs of this particular group of people and the current activities undertaken by the Polish state. The work defines the concept of space, mainly public space, and architectural accessibility. Both the legal and organizational conditions created to ensure architectural accessibility were characterized.
Keywords: space, architectural accessibility, people with disabilities, universal design